White teacher with a new preface - Paley, Vivian Gussin 1929- (Harvard University Press, 2000)
Publisher's description: Vivian Paley presents a moving personal account of her experiences teaching kindergarten in an integrated school within a predominantly white, middle-class neighborhood. In a new preface, she reflects on the way that even simple terminology can convey unintended meanings and show a speaker's blind spots. She also vividly describes what her readers have taught her over the years about herself as a "white teacher."